Islamic Economic-Based Home Industry Development Strategy Using SOAR Analysis - Purba, Febri Andriawan; Yanti, Nursantri; Ilhami Nasution, Muhammad lathief (Universitas Ibn Khladun Bogor, 2025)
This study aims to analyze the development strategy of home industries based on Islamic economics using the SOAR (Strengths, Opportunities, Aspirations, and Results) analysis approach, with a case study on the rattan basket business in Kualuh Selatan District. The rattan basket home industry has significant economic potential due to its foundation in local wisdom and alignment with Islamic economic principles such as justice, blessing, and collective welfare. This research uses a qualitative method with data collected through literature reviews and direct interviews with local craftsmen. The findings indicate that the main strengths of the business lie in the availability of raw materials and the skills of the artisans, while opportunities include increasing market demand and government support. The result is this business relies on traditional skills and local raw materials, and makes a significant economic contribution to the surrounding community. However, various obstacles remain, such as limited capital, traditional equipment, and limited market access. Using the SOAR (Strengths, Opportunities, Aspirations, Results) analysis approach, this study shows that internal strengths such as artisan skills and abundant raw materials can be combined with external opportunities such as government support and digital marketing. The aspiration to improve product quality, expand employment opportunities, and introduce modern technology are the main drivers for this business’s development.